在(x2+x+1)n=
(1)写出三项式的2次系数列和3次系数列; (2)列出杨辉三角形类似的表(0≤n≤4,n∈N),用三项式的n次系数表示
(3)用二项式系数表示
|
(1)在( x2+x+1 )n=
x2 n+D 0n
x2 n-1+D 1n
x2 n-2+…+D 2n
x+D 2 n-1n
的展开式中,D 2 nn
∵(x2+x+1)2=x4+x2+1+2x3+2x2+2x=x4+2x3+3x2+2x+1,
∴
=1 , D 02
=2 , D 12
=3 , D 22
=2 , D 32
=1.D 42
∵(x2+x+1)3=(x4+2x3+3x2+2x+1)(x2+x+1)=x6+3x5+6x4+7x3+6x2+3x+1,
∴
=1 , D 03
=3 , D 13
=6 , D 23
=7 , D 33
=6 , D 43
=3 , D 53
=1.D 63
(2)列出杨辉三角形类似的表(0≤n≤4,n∈N): 1 1 1 1 1 2 3 2 1 1 3 6 7 6 3 1 1 4 10 16 19 16 10 4 1
=D 0n+1
=0 , D 0n
=D 1n+1
+D 1n
=n+1 , D 0n
=D k+1n+1
+D k-1n
+D kn
( 1≤k≤2 n-1 ).D k+1n
(3)用二项式系数表示
:D 3n
=1 , D 21
=D 22
+D 01
+D 11
=3=D 21
, C 23
=D 23
+D 02
+D 12
=6=D 22 C 24
=D 24
+D 03
+D 13
=10=D 23
, …C 25
可得
=D 2n-1
+D 0n-2
+D 1n-2
=1+n-2+D 2n-2
=C 2n-1
.C 2n
∵
=D 3n
+D 1n-1
+D 2n-1
,D 3n-1
∴
-D 3n
=D 3n-1
+D 1n-1
=D 2n-1
+C 1n
-1=C 2n
-1.C 2n+1
∵
-D 33
=D 32
-1,C 24
-D 34
=D 33
-1,C 25
-D 35
=D 34
-1,… , C 26
-D 3n
=D 3n-1
-1,C 2n+1
∴
-D 3n
=D 32
+C 24
+C 25
+…+C 26
-( n-2 )C 2n+1
=(
-C 35
)+( C 34
-C 36
)+( C 35
-C 37
)+…+( C 36
-C 3n+2
)-( n-2 )=C 3n+1
-C 3n+2
-( n-2 )C 34
=
-( n+2 ).C 3n+2
∴
=D 3n
-C 3n+2
.C 1n